The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2013
DOI: 10.1111/ene.12222
|View full text |Cite
|
Sign up to set email alerts
|

N‐terminal pro‐brain natriuretic peptide level determined at different times identifies transient ischaemic attack patients with atrial fibrillation

Abstract: High levels of NT-proBNP determined during the first 3 months after a TIA were associated with AF. Consequently, this biomarker may be useful to reclassify undetermined TIA patients as having disease of CE.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
18
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 15 publications
0
18
0
Order By: Relevance
“…Because of unavailability of the requested data or lack of response from authors, we finally selected 23 articles (Figure 1). [16][17][18][19][20][21][22][23][30][31][32][33][34][35][36][37][38][39][40][41][42][43][44] The median quality score was 9 (minimum=5 and maximum=11; data not shown). These 23 included articles corresponded to 18 different cohorts of patients, 16 of which had data from patients with a defined cause (cardioembolic, LAA, or SVD) and 2 cohorts containing data of undetermined patients only.…”
Section: Resultsmentioning
confidence: 93%
See 1 more Smart Citation
“…Because of unavailability of the requested data or lack of response from authors, we finally selected 23 articles (Figure 1). [16][17][18][19][20][21][22][23][30][31][32][33][34][35][36][37][38][39][40][41][42][43][44] The median quality score was 9 (minimum=5 and maximum=11; data not shown). These 23 included articles corresponded to 18 different cohorts of patients, 16 of which had data from patients with a defined cause (cardioembolic, LAA, or SVD) and 2 cohorts containing data of undetermined patients only.…”
Section: Resultsmentioning
confidence: 93%
“…15 This relation between pro-BNP and atrial dilatation explains the clear association of elevated BNP/NT-proBNP with the presence of AF 15 and cardioembolic stroke. [16][17][18][19][20][21][22][23] Both natriuretic peptides have been associated with cardioembolic stroke in several, but generally small studies, [16][17][18][19][20][21][22][23] reporting different cutoff points to distinguish cardioembolic from noncardioembolic stroke and considering different time points from symptoms onset. A clear association of BNP/NT-proBNP with cardioembolic stroke cause would allow to complement and speedup the diagnosis of cardioembolism stroke especially in the most challenging cases (ie, paroxysmal AF) and might aid to reduce the rate of undetermined strokes.…”
mentioning
confidence: 99%
“…NT‐proBNP coexists in circulation with brain natriuretic peptide (BNP) in equal proportion. It has been associated with the diagnosis of atrial fibrillation among TIA patients and with poor prognosis after ischaemic stroke . Finally, copeptin is a peptide of 39 amino acids in the C‐terminal part of pro‐vasopressin, is secreted together with vasopressin during processing of the precursor peptide by the neurohypophysis upon hemodynamic or osmotic stimuli and is involved in the endocrine stress response like brain ischaemia .…”
Section: Discussionmentioning
confidence: 99%
“…Our prospective study evaluated the correlation of a panel of different biomarkers with infarct size. We combined biomarkers of in ammation, atrial dysfunction and neuronal and glial dysfunction [5][6][7] and observed that IL-6 and S100b levels were able to independently predict infarct volume. In contrast to the other biomarkers, their correlation remained unchanged after the multivariate analyses adjusted for stroke aetiology.…”
Section: Discussionmentioning
confidence: 99%